Улс төрийн судалгаанд математик загварчлалын арга хэрэглэх нь - Б.Эрдэнэдалай, (Politology, 2023)
Some professors of political science are noted that mathematical methodologies importance to need political research. Their book "Political research method" noted modelling political processes. First, The Richardson model is the most widely studied dynamic model in international relations and, with the possible exception of the incremental budgeting model, the whole of political science. Second, The main purpose of using game theory is to draw up plans of action for the rational behavior of the players involved. The plans represent optimal strategies for each player. Game theory provides a number of theorems applicable to studies of choices of different military strategies. Third, Downs presents a rational calculus of voting that has inspired much of the later work on voting and turnout. Particularly significant was his conclusion that a rational voter should almost never bother to vote. Mongolian some universities, governmental organizations, non-govermental organizations and political parties are researching election results and public opinion. They usually use this research works mathematical method.